OGLE-2017-BLG-1434Lb: Eighth q<1×10-4 mass-ratio microlens planet confirms turnover in planet mass-ratio function - Udalski, Andrzej; Hundertmark, Markus (Arxiv, 2018)
We report the discovery of a cold Super-Earth planet - (mp=4.4±0.5 M⊙) orbiting a low-mass - (M=0.23±0.03) M⊙ dwarf at projected separation - a⊥=1.18±0.10 a.u., i.e., about 1.9 times the - distance the snow line. The system is quite nearby for a microlensing - planet, DL=0.86±0.09 kpc. Indeed, it was the large - lens-source relative parallax πrel=1.0 mas (combined with - the low mass M) that gave rise to the large, and thus well-measured, - "microlens parallax" - πE∝(πrel/M)1/2 that enabled - these precise measurements. OGLE-2017-BLG-1434Lb is the eighth - microlensing planet with planet-host mass ratio - q<1×10-4. - - We apply a new planet-detection sensitivity method, which is a variant - of "V/Vmax", to seven of these eight planets to derive the - mass-ratio function in this regime. We find dN/d lnq ∝ - qp, with p=1.05+0.78-0.68, which - confirms the "turnover" in the mass function found by Suzuki et al. - relative to the power law of opposite sign n=-0.93±0.13 at higher - mass ratios q≳2×10-4. We combine our result with - that of Suzuki et al. to obtain p=0.73+0.42-0.34.